Arzneimitteltherapieanamnese in Zeiten von COVID-19: Nutzung von Krankenkassendaten zur Vermeidung von Medikationsfehlern - Dörje, Frank; Grandt, Daniel; Picksak, Gesine; Klaas, Christoph (Krankenhauspharmazie, 2020)
Infections by SARS-CoV-2 face hospitals with enormous challenges, also when it comes to the anamnesis of drug therapy. In medical emergencies the hospitalisation of patients, not only with infections by SARS-CoV-2, has to take place fast and often without the possibility to recourse the documents of the referring physicians. Currently the German health insurance funds BARMER and AOK Nordwest, offers all hospitals free access to their billing data to support a better anamnesis of current diagnoses, therapy, medical history and actual medication of their patients. These information were summarized and are presented in a clear and structured form to enable the attending physicians and clinical pharmacists a rapid impression of the patients medical history. Because one of the leading courses of medication errors in hospital is based on incomplete medication history, the additional information by health insurance funds can support the attending team of physicians and pharmacists to minimize actual medication errors ensuring a safe drug therapy for the patient during his hospitalization. The evaluation of the benefits of this type of information provision is also part of a project funded by a fund for innovations of the G-BA (TOP - "Transsectoral optimization of patient safety").
CRIS-Team Scopus Importer:2021-04-19
Keywords: Billing data from health insurance funds; COVID-19; Medical history; Medication errors; TOP - trans-sectoral optimization of patient safety